2023
DOI: 10.1111/age.13305
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic diversity and selection signals in Chaling cattle of southern China using whole‐genome scan

Abstract: China has diversified resources of indigenous cattle, which are classified into Northern, Central, and Southern groups according to their geographical distribution. Chaling cattle belong to Southern group. This breed is famous for the production of good quality meat with elite meat grades. To analyze the genetic diversity of Chaling cattle, 20 samples were sequenced using whole‐genome resequencing technology, along with 138 published whole‐genome sequencing data of Indian indicine cattle, Chinese indicine catt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…Commercial breeds/populations with a long breeding history, such as East Asian taurine cattle, European taurine cattle and Eurasian taurine cattle, generally have lower nucleotide diversity. At the same time, the nucleotide diversities of North Chinese cattle breeds are all higher than that of these commercial cattle breeds/populations, which is consistent with previous research results (Guan et al., 2022; Li et al., 2023; Liu et al., 2022; Luo et al., 2022; Mei et al., 2018; Xia, Zhang, et al., 2021). In the North Chinese cattle, the nucleotide diversity of Qaidam cattle is higher than that of the other four breeds.…”
Section: Discussionsupporting
confidence: 90%
“…Commercial breeds/populations with a long breeding history, such as East Asian taurine cattle, European taurine cattle and Eurasian taurine cattle, generally have lower nucleotide diversity. At the same time, the nucleotide diversities of North Chinese cattle breeds are all higher than that of these commercial cattle breeds/populations, which is consistent with previous research results (Guan et al., 2022; Li et al., 2023; Liu et al., 2022; Luo et al., 2022; Mei et al., 2018; Xia, Zhang, et al., 2021). In the North Chinese cattle, the nucleotide diversity of Qaidam cattle is higher than that of the other four breeds.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, WGS analysis of domestic cattle revealed that cattle worldwide can be divided into five continental groups: European taurine, Eurasian taurine, East Asian taurine, Chinese indicine, and Indian indicine (Chen et al., 2018). Many studies have employed WGS to analyze the unique adaptability of native Chinese cattle breeds (Chen et al., 2021; Lyu, Guan, et al., 2023; Lyu, Ren, et al., 2023; Shen et al., 2022) and identified a range of representative genes and signaling pathways. In the past, limited research has been performed on the genome diversity and population structure of the Anxi cattle breed's mtDNA and Y chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Whole‐genome sequencing (WGS) is an effective technique/tool for identifying population structures and genetic variations that influence economic traits in livestock (Li et al., 2023). A global analysis of domestic cattle using WGS identified five distinct continental groups: European taurine, Eurasian taurine, East Asian taurine, Chinese indicine and Indian indicine (Chen et al., 2018).…”
Section: Introductionmentioning
confidence: 99%